Transformasi Keamanan Maritim Indonesia melalui Penerapan Teknologi Blockchain - Nadine Pratiwi Kadir Maricar; Wira Atman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Maritime security in Indonesia faces numerous challenges, including piracy, smuggling, and environmental degradation that threaten the sustainability of the maritime sector. Blockchain technology, known for its transparency, security, and efficiency, presents a potential solution to enhance maritime security systems in Indonesia. This study explores the application of Blockchain technology in improving surveillance, tracking, and data validation in the maritime sector. By analyzing existing literature and case studies, the research identifies how Blockchain can strengthen security systems through smart contracts, real-time supply chain tracking, and increased transparency in maritime transactions. The study also discusses the challenges of implementing Blockchain technology in Indonesia's maritime sector and offers recommendations to accelerate its adoption. The findings aim to provide insights for policymakers and practitioners in developing technology-driven solutions to enhance maritime security in Indonesia.